Effect of pregnancy prolongation in early‐onset pre‐eclampsia on postpartum maternal cardiovascular, renal and metabolic function in primiparous women: an observational study. (13th August 2020) - Mulder, EG; Ghossein‐Doha, C; Crutsen, JRW; Van Kuijk, SMJ; Thilaganathan, B; Spaanderman, MEA
Abstract : Objective: To evaluate the association between deferred delivery in early‐onset pre‐eclampsia and offspring outcome and maternal cardiovascular, renal and metabolic function in the postpartum period. Design: Observational study. Setting: Tertiary referral hospital. Population: Nulliparous women diagnosed with pre‐eclampsia before 34 weeks' gestation who participated in a routine postpartum cardiovascular risk assessment programme. Women with hypertension, diabetes mellitus or renal disease prior to pregnancy were excluded. Methods: Regression analyses were performed to assess the association between pregnancy prolongation and outcome measures. Main outcome measures: Offspring outcome and prevalence of deviant maternal cardiovascular, renal and metabolic function. Results: The study population included 564 women with a median pregnancy prolongation of 10 days (interquartile range [IQR] 4–18) who were assessed at on average 8 months (IQR 6–12) postpartum. Pregnancy prolongation after diagnosis resulted in a decrease in infant mortality (adjusted odd ratio [aOR] 0.907, 95% CI 0.852–0.965 per day prolongation). This improvement in offspring outcome was associated with an elevated risk of moderately increased albuminuria (aOR 1.025, 95% CI 1.006–1.045 per day prolongation), but not with aberrant cardiac geometry, cardiac systolic or diastolic dysfunction, persistent hypertension or metabolic syndrome. Conclusion: Pregnancy prolongation in early‐onset pre‐eclampsia is associated with improved offspring outcome and survival. These effects do not appear to be deleterious to short‐term maternal cardiovascular and metabolic function but are associated with a modest increase in risk of residual albuminuria. Tweetable abstract: Pregnancy prolongation in pre‐eclampsia has only a limited effect on postpartum maternal cardiovascular function. Tweetable abstract: Pregnancy prolongation in pre‐eclampsia has only a limited effect on postpartum maternal cardiovascular function.